Kepuasan Kerja Tenaga Medis pada Era Jaminan Kesehatan Nasional - Nur Fadhilah Arifin; Syahrir A. Pasinringi; Basir Palu (Media Kesehatan Masyarakat Indonesia, 2018)
Medical personnel as the spearhead of hospital services deeply feel the change in health care system inNational Health Insurance (NHI) era that implements the system of quality control and cost control. The aimof the research was to explore the employee satisfaction of medical personnel in the era of the National HealthInsurance in Regional Public Hospital of Sinjai. The research was a descriptive qualitative study with a case studyapproacch. The informants were medical personnel as functional personnel. To obtain additional information ascomparison, the researcher also interviewed the director, the head of service and nursing unit, the head of financialsub-unit, and Sisrute officials in Regional Public Hospital of Sinjai. The data were obtained through indepthinterview, observation and documentation. The result of the research indicate the service system in the era ofNational Health Insurance is good, but its implementation has not runas it is expected. The cooperation betweenBPJS and Regional Public Hospital of Sinjai is considered slow and inconsistent and sometimes the problemsolving is not followed up. Medical personnel in Regional Public Hospital of Sinjai is satisfied with transparencyof medical service division, but the number of Ina CBGs packages are still under the standar and time of paymentof medical service is late.